Dampak Sibling Rivalry terhadap Kepribadian Anak Usia Dini - jannah, Redatul; Z, Sri Putri Rahayu (Jurnal Ilmiah Psikomuda (JIPM) Connectedness, 2023)
Sibling rivalry is a form of relationship between siblings who feel that their siblings are enemies. Sibling rivalry, maybe there are still many people who consider it trivial, even though the impact of sibling rivalry itself greatly impacts the growth and development of future children. If sibling rivalry is not overcome, it will grow in children so that good sibling relationships are not created. In this case, the authors conducted research using the library research method on how the impact of sibling rivalry has on the formation of a child's personality because it is known that a child's personality will be formed from childhood and from his childhood past. The impact of sibling rivalry is shared by some of them on oneself, siblings and others. However, not all sibling rivalries have a negative impact, some have a positive impact. In this case, it is hoped that parents can understand and understand what their children feel to anticipate sibling rivalry.